PENGARUH GAYA HIDUP HEDONISME DI MASA COVID-19 TERHADAP KEPUTUSAN MEMBELI DI TOKOPEDIA PADA PENGGUNA TOKOPEDIA - Eric (2023)
The Covid-19 pandemic has also had an impact on Indonesia, which is caused by a virus that can attack the immune system and spread easily. This pandemic has been able to change people's lifestyles, especially in meeting their needs. During the COVID-19 pandemic, it also resulted in a higher ercentage of public spending. Even though people have lost their jobs and students don't get pocket money every month, they are able to buy necessities and only follow the trend that occurred during the COVID-19 pandemic. The more often someone spends their time at home, they tend to access the online shop, increasing their buying behavior, which results in quick and sudden (impulsive) purchases, and vice versa, the less often someone spends time accessing the online shop, resulting in a buying decision that will result in purchases quickly and suddenly (impulsive). The theory used is the theory of information integration (information integration theory) and consistency, this theory is a theory that is in a group of thoughts or cybernic traditions, and uses quantitative research methods by taking data samples through estionnaires. The results showed that the hedonistic lifestyle had a significant positive effect on purchasing decisions, where the higher the influence of the hedonistic lifestyle, the higher the decision to buy at Tokopedia for Tokopedia users, with a contribution of 62.0%, while the remaining 38.0% is the influence or contribution of other variables not examined outside the study.